2018
DOI: 10.1042/bsr20181128
|View full text |Cite
|
Sign up to set email alerts
|

Association between the polymorphisms of CALM1 gene and osteoarthritis risk: a meta-analysis based on observational studies

Abstract: The existing studies on the association between polymorphisms of Calmodulin 1 (CALM1) gene and the risk of osteoarthritis (OA, a complex multifactorial disease and a major degenerative form of arthritis) in different populations have yielded conflicting findings. Therefore, we conducted a meta-analysis by systematically searching PubMed, Embase, Medline, Cochrane Library and Google Scholar, and assessing this association by calculating pooled odds ratios with 95% confidence intervals. Subgroup analyses stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…This results in decreased expression of matrix genes, and hence, chondrocytes are unable to respond to mechanical stress. This genotype has been found associated with hip OA (HOA) in the Japanese population and associated to OA in a meta-analysis done using six-control case studies [14,16]. However, a similar study done on British population and five case-control studies meta-analysis revealed no association with it [17,18].…”
Section: Introductionmentioning
confidence: 97%
“…This results in decreased expression of matrix genes, and hence, chondrocytes are unable to respond to mechanical stress. This genotype has been found associated with hip OA (HOA) in the Japanese population and associated to OA in a meta-analysis done using six-control case studies [14,16]. However, a similar study done on British population and five case-control studies meta-analysis revealed no association with it [17,18].…”
Section: Introductionmentioning
confidence: 97%
“…Osteoarthritis (OA; OMIM 165720) is documented as the basic form of arthritis and can originate from progressive loss of joint function. 1 Disjoint of hip and knee leads to the major cause of pain, functional loss, and poor quality of life. 2 It is also documented as a late-onset musculoskeletal disease in the elder population, characterized by gradual degradation of the articular cartilage by additional synovium injury, subchondral, and other types of bone-joint tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Одним из наиболее часто встречающихся первичных клинических проявлений дисфункции миокарда считают различные варианты аритмий [4]. К опасным состояниям для пациентов, находящихся в процессе терапии противоопухолевыми препаратами, следует отнести удлинение интервала QT, расстройство электрической активности сердца [5].…”
unclassified